Rectal Foreign Bodies: What Is the Current Standard? - Cologne, Kyle G.; Ault, Glenn T. (Clinics in Colon and Rectal Surgery, 2012)
Rectal foreign bodies represent a challenging and unique field of colorectal trauma. The approach includes a careful history and physical examination, a high index of suspicion for any evidence of perforation, a creative approach to nonoperative removal, and appropriate short-term follow-up to detect any delayed perforation.
Keywords: rectal foreign bodies; rectal trauma; rectal perforation; rectal repair; transanal approach; endoscopy